Pengaruh Konflik Kerja Dan Stres Kerja Terhadap Kinerja Karyawan Pada PT Prima Karya Sarana Sejahtera Cabang Jakarta 3 (BSD) Serpong Tangerang Selatan - Triwan Fajar Zai; Kamsidik Kamsidik (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The purpose of this study is to determine the effect of work conflict and work stress on employee performance at PT Prima Karya Sarana Sejahtera Jakarta 3 Branch (BSD), both partially and simultaneously. The type of research in this study is quantitative with an associative approach. The population used in this study were employees at PT Prima Karya Sarana Sejahtera Jakarta 3 Branch (BSD). In this study, the population was 60 employees at PT Prima Karya Sarana Sejahtera Jakarta 3 Branch (BSD) and the number of samples in this study was 60 respondents. The data analysis technique used multiple linear regression and was assisted by the SPSS program. The results of this study indicate that Work Conflict partially influences employee performance, with a regression equation of Y = 8.878 + 0.754 X1, and a calculated t-value > t-table, or (7.767 > 2.001). Therefore, H0 is rejected and Ha is accepted, indicating a significant influence of the Work Conflict variable on employee performance. Partially, Work Stress influences Employee Performance, with a regression equation of Y = 5.673 + 0.860 X2, and a calculated t-value > t-table, or (9.580 > 2.001). Therefore, H0 is rejected and Ha2 is accepted, indicating a significant influence of Work Stress on Employee Performance. Simultaneously, Work Conflict and Work Stress significantly influence Employee Performance, with a regression equation of Y = 4.376 + 0.242 X1 + 0.656 X2. The calculated F-value > F-table, or (48.624 > 2.766).